Vertical and horizontal room cosmology in traditional house (sa’o) Adat Saga Village, Ende Regency, Flores - Antariksa; Zulkifli H. Achmad; Agung Murti Nugroho (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2017)
Cosmology is the science related to kemestaan (cosmos) in a concept of the relationship between the human world (micro-cosmos) and of the universe. Space in traditional house Saga has values and khasan interesting architecturally is examined. The influence of Ngga'e on the Du'a belief and traditional home space Saga interesting architecturally is identified. This study uses qualitative methods with an ethnographic approach that is description. The findings of this study is about the cosmology of the space on a traditional home. Cosmological view of space in traditional house Saga is distinguished into three parts namely is lewu, gara as one and mention the position of the human body parts. Cosmological view of space in traditional Indigenous Villages (Sa'o) Saga depicted horizontally with the mother lay. Nature of traditional house Saga is the core of fertility and birth. Being a mother is clearly visible on a carved door (pene ria) enter Sa'o believe carving the breasts of a woman who symbolizes the human life and a transverse under IE peneria koba leke symbolizing the human development. The position of the head of the mother at the lulu (the dugout), second legs on his back is to the fore in the tent (dugout or accepting guests), second hand mereba is at the right and left dhembi space, the womb or humanitarian space are at puse ndawa.